DETERMINAN TINGKAT MORTALITAS DI PROVINSI SUMATERA BARAT - Elvia Desra; Idris Idris (Universitas Negeri Padang, 2019)
This study aims to determine: (1) the influence of maternal education level on mortality rates in West Sumatra. (2) the influence of maternal age on mortality rates in West Sumatra. (3) the effect of the health budget on mortality rates in West Sumatra. (4) the influence of medical personnel on mortality rates in West Sumatra. The type of research used is descriptive and associative. The type of data used is secondary data. This study uses panel data, namely using 19 districts / cities in West Sumatra Province using the Random Effect Model (REM) approach. The results of this study indicate that: (1) The level of maternal education has a negative and significant effect on mortality in West Sumatra, (2) Maternal age has a negative and not significant effect on mortality rates in West Sumatra, (3) Health budgets have a positive and insignificant effect against mortality rates in West Sumatra, (4ss) Medical personnel have a positive and not significant effect on mortality rates in West Sumatra.